The aftermath of the milk scandal of 2008 :the challenges of Chinese systemic governance and food safety regulation. - Li, Yanjie (2015)
Food safety problems set an enormous challenge to China’s sustainable economic development. The Milk Scandal of 2008 brought public attention to the poor regulation and ineffective administration of the food industry. This highlighted the fact that food safety is relevant to the public health and the brand ‘Made in China’ in international trading. It also shows how food safety law and better environmental protection has arisen out of a crisis. The milk scandal brought an influx of foreign products into China and opened up the Chinese market to international influence and food standards that would not have been possible before the crisis began. Sustaining China’s environmental future is a work-in-progress with uncertain outcomes but there is an admission that without solving the food safety problem, China cannot achieve its sustainable economic development. This thesis examines China’s current food safety legislation in the aftermath of the milk scandal of 2008. The thesis raises the question of how China deals with its food safety crisis and regulates its food industry to cope with its sustainable economic development. It also considers how best for the Chinese and the rest of the world may be able to learn from the Chinese experience. In the aftermath of the Chinese food crisis, China found itself subject to imports from abroad. This had a two-fold effect. It brought international regulatory practices into Chinese life; the second effect was to awaken China to the demands of international trade and the need to conform to best practice. It also showed how China had to meet expectations that were informed by international experience, which China sadly lacked. A deeper analysis is that China was exposed to the dilemma of profit driven organisations failing to appreciate the role of regulation and the safety of ordinary people. The scandal exposed many institutional and organisational shortcomings while the lessons were clear for anyone who looked. Placing profits over the preservation of social order and stability resulted in short-term gains with few long term benefits. This research provides a comprehensive analysis and offers a perspective of the Chinese food safety problem from the legal, social and economic context of the problem. The causes of the food safety problem in China are complex. The food safety problem is not only caused by the defect of the food safety legislation itself. Other factors, such as environmental challenges and the irresponsible business activities, all contribute to the ineffectiveness of the food safety regulatory system. The thesis starts with the Milk Scandal of 2008 to examine the current food safety regulatory system in China. It addresses the main systemic problem, which leads to the weak implementation and ineffective administrations, and it also finds out that apart from the systemic defects, the environmental problem and the failure of the private sector all have an impact on the food safety regulatory system. Furthermore, the thesis also explores the new innovations in the 2014 Environmental Protection Law, which may potentially contribute to the food safety law in the future. The private sector has also been examined. The fact is found that Chinese companies are operated in an irresponsible way, which causes the consecutive food scandals in China. The role of corporate social responsibility is also considered to guide the business activities in practice. The interests of the stakeholders, such as consumers, need to be addressed in the decision-making. The final conclusion is China still has a long way to go to achieve its sustainable economic development. The legislation system needs to be completed and unified. The effectiveness of the administration needs to be improved and independent judiciary needs to be built up. Besides the systemic problem, the improvement of the environment and the responsible business operation also contribute to re-shaping an effective food safety regulatory system. The innovation in the Environmental Law of 2014 can also be introduced to the food safety system. The citizen-driven approach can be used as an important supplement to China’s traditional state-centred approach, to overcome the systemic weakness in the implementation of the food safety law. Many disasters in the world are discussed in terms of the experiences countries may gain from bad events. Bhopal and Chernobyl are two examples. The Chinese Milk Scandal stands in a line of disasters such as BSE in Britain that have re-oriented the regulatory map. Stakeholders and citizens have much to gain from learning the lessons of the milk scandal.